2022
DOI: 10.1155/2022/5760674
|View full text |Cite
|
Sign up to set email alerts
|

Research on Mechanical Response of Polymer Grouting Repair for Longitudinal Cracks in Reconstructed and Expanded Expressway Pavement

Abstract: Polymer grouting materials have been widely used in road repair projects. In order to study the application of polymer grouting materials in repairing the joint cracks and voids of new and old subgrades in the reconstruction and expansion projects of expressways. According to the phenomenon investigation data, ABAQUS finite element software was used to establish a three-dimensional road mechanical response analysis model, and the mechanical response characteristics of the road before and after polymer grouting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…It has been reported that the NRFP grouting material has an expansion volume ratio of 10–20 and a permeability coefficient of 10 −8 cm/s, and it is environmentally friendly [ 6 ]. By virtue of these superior material properties, NRFP grouting material has found its applications in the non-excavation rehabilitation of expressway pavement [ 7 ], underground pipes [ 8 ], and foundations [ 9 , 10 ], as well as building water barriers.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the NRFP grouting material has an expansion volume ratio of 10–20 and a permeability coefficient of 10 −8 cm/s, and it is environmentally friendly [ 6 ]. By virtue of these superior material properties, NRFP grouting material has found its applications in the non-excavation rehabilitation of expressway pavement [ 7 ], underground pipes [ 8 ], and foundations [ 9 , 10 ], as well as building water barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Fang et al showed through experiments that polymers can efectively repair the settlement of high-speed railways and provide sufcient long-term durability under dynamic train loads [19,20]. Te research of Li et al shows that high polymer can efectively repair cracks and voids in pavement and efectively prevent pavement settlement [21,22]. Te polymer grouting material can sufciently and densely fll the damaged area, thereby controlling the unfavorable deformation and better restoring the structural integrity.…”
Section: Introductionmentioning
confidence: 99%